Shudi Pingchan Decoction combined with repetitive transcranial magnetic stimulation in the treatment of Parkinson's disease with sleep disorders - Qing Ye; Xiqun Chen; Yuqing Hu; Jie Zhou; Chen Gao; Zhenguo Liu (World Scientific Publishing, 2020)
Objective: To investigate the effects of "Shudi Pingchan Decoction" combined with repetitive transcranial magnetic stimulation (rTMS) on sleep disorders in Parkinson's disease (PD). Methods: A randomized, single-blind, placebo/sham-controlled trial was performed on 144 PD patients with sleep disorders. Participants were randomized into rTMS (rTMS with placebo decoction), Chinese medicine (Shudi Pingchan Decoction with sham stimulation), or Shudi Pingchan Decoction combined with rTMS group over a 12-month course. The efficacy was evaluated by Unified Parkinson's Disease Rating Scale (UPDRS) I-IV scores, cardiopulmonary coupling (CPC) sleep quality assessment, Hamilton Depression Scale (HAMD), and Hamilton Anxiety Scale (HAMA). Results: (1) After 12 weeks of treatment, rTMS treatment group showed markedly improved UPDRS I score, whereas Chinese medicine treatment group reported improved UPDRS II and UPDRS III scores than rTMS. At the same time, combined therapy improved the UPDRS I-III scores. (2) CPC sleep quality assessment showed that compared with baseline before treatment, sleep latency was significantly shortened after 12 weeks of Chinese medicine treatment. In the rTMS group, the scores of sleep awakening period were significantly decreased after six weeks and 12 weeks of treatment. The total sleep time was significantly extended after six weeks and 12 weeks of treatment in both groups. The sleep-improving effect was stronger in combined treatment group than the single treatment groups after 12 weeks of treatment. (3) Compared with baseline before treatment, the HAMD scores of rTMS group were significantly lower at six weeks and 12 weeks, the HAMA scores of Chinese medicine treatment group were significantly lower at 12 weeks, and the combined treatment resulted in stronger effects. Conclusion: The combined treatment of "Shudi Pingchan Decoction" with rTMS has significant curative effect on PD complicated with sleep disorders, and the combined therapy has complementary advantages.